تأثير تقنية Blockchain في تعزيز تطبيق التدقيق الإلكتروني: دراسة استطلاعية لآراء عينة من الأكاديميين والمدققين في جامعة الموصل - العلي، ماجد يعقوب محمود; النعيمي، عبدالواحد غازي محمد; منصور، علي يوسف أحمد الملا; الدليمي، عبدالرحمن عبدالله محمد (جامعة تكريت - كلية الإدارة والاقتصاد, 2023)
يهدف البحث إلى تحديد مدى تأثير تقنية بلوكتشين في تعزيز تطبيق التدقيق الإلكتروني في جامعة الموصل وانطلق البحث من السؤال الرئيس المتمثل بالكشف عن مدى تأثير استخدام تقنية بلوكتشين في تعزيز تطبيق التدقيق الإلكتروني، وقد اعتمد الباحثين في إجراء بحثهم على المنهج الوصفي التحليلي على عينة من الأكاديميين والمدققين في جامعة الموصل، إذ تم الاعتماد على استمارة استبيان، بغية جمع البيانات عن طريق توزيع (45) استمارة، وتم استرداد (39) استمارة، وتم اختبارها عن طريق مجموعة من البرامج الإحصائية تتمثل ب (EXCEL) و(SPSS 23). وتوصل البحث إلى مجموعة من الاستنتاجات، من أهمها استخدام تقنية Blockchain يعطي الثقة والأمان للزبائن الخاضعين لعملية التدقيق لوجود ميزة التشفير التي لا تسمح بأي حذف أو تعديل في بيانات العملية مما يحد من حدوث أي حالة غش أو احتيال بشري، وأظهرت نتائج التحليل الإحصائي إلى وجود علاقة تأثير بين تقنية Blockchain والتدقيق الإلكتروني، فضلا عن تقديم توصيات من أهمها تنمية وتطوير برامج وأساليب التدقيق بما يتطابق مع تقنيات وتكنولوجيا المعلومات الحديثة. The research aims to determine the extent of the impact of Blockchain technology in enhancing the application of electronic auditing at the University of Mosul. The research started from the main question of revealing the extent of the impact of the use of Blockchain technology in enhancing the application of electronic auditing. In conducting their research, the researchers relied on the descriptive analytical approach on a sample of academics and auditors. At the University of Mosul, a questionnaire form was relied upon in order to collect data by distributing (45) questionnaires. (39) questionnaires were retrieved and tested using a set of statistical programs represented by (EXCEL) and (SPSS 23). The research reached a set of conclusions, the most important of which is the use of Blockchain technology that gives confidence and security to customers subject to the audit process due to the presence of the encryption feature that does not allow any deletion or modification of the transaction data, which limits the occurrence of any case of fraud or human fraud. The results of the statistical analysis showed that there is a relationship The impact between Blockchain technology and electronic auditing, in addition to providing recommendations, the most important of which is the development of audit programs and methods in accordance with modern information techniques and technology.
Keywords: تكنولوجيا المعلومات -- العملات الافتراضية -- عمليات التدقيق -- العراق